A bitter revolution : China's struggle with the modern world - Mitter, Rana, 1969- (Making of the modern world., 2005)
China is now poised to take a key role on the world stage, but in the early twentieth century the situation could not have been more different. Rana Mitter goes back to this pivotal moment in Chinese history to uncover the origins of the painful transition from a premodern past into a modern world. Mitter takes us through the resulting social turmoil and political promise, the devastating war against Japan in the 1940s, Communism and the Cultural Revolution of the 1960s, and the new era of hope in the 1980s ended by the Tian'anmen uprising. He reveals the impetus behind the dramatic changes in.